Database Cloud Storage : the essential guide to Oracle automatic storage management - Vengurlekar, Nitin; Bagal, Prasad (New York : McGraw-Hill Education, 2013)
"A complete solutions guide to Oracle Automatic Storage Management (ASM) and overall cloud storage management. Oracle Cloud Storage Management contains the latest information on the inner-workings of Oracle ASM and Oracle's overall cloud storage management strategy. This Oracle Press guide explains how to build and manage a scalable cloud storage infrastructure with Oracle ASM. You'll learn how to configure cloud storage solutions, build disk groups, use data striping and mirroring, and optimize performance. Details on ensuring consistency across server and storage platforms, maximizing data redundancy, and administering Oracle ASM are also included. Fully covers Oracle Exadata integration Offers a comprehensive understanding of why cloud storage management is critical to modern storage, and how to harness and integrate Oracle ASM Covers practical day-to-day usage, general operations, best practices, and tips & techniques Written by members of the team who developed and managed Oracle ASM/cloud storage management "--
"Build and manage a scalable, highly available cloud storage solution. Filled with detailed examples and best practices, this Oracle Press guide explains how to set up a complete cloud-based storage system using Oracle Automatic Storage Management. Find out how to prepare hardware, build disk groups, efficiently allocate storage space, and handle security. Database Cloud Storage: The Essential Guide to Oracle Automatic Storage Management shows how to monitor your system, maximize throughput, and ensure consistency across servers and clusters"--
Machine generated contents note: -- 1) Database Consolidation into Private Clouds -- 2) Oracle Database Cloud Strategy -- 3) ASM and Grid Infrastructure -- 4) ACFS Design and Deployment -- 5) ACFS Data Services -- 6) ASM Instance -- 7) ASM Disks and Diskgroups -- 8) ASMLIB Concepts and Overview -- 9) ASM Files, Aliases, and Security -- 10) ASM and Space Allocation -- 11) ASMLIB Concepts and Overview -- 12) ASM Operations -- 13) ASM Persistent Data Structures -- 14) ASM and Database integration -- 15) ASM Optimizations in Oracle Engineered Solutions -- 16) ASM optimization for Engineered Solutions (Exadata and ODA) -- 17) ACFS Data Services -- 18) ASM and 3rd Party Integration -- 19) ACSF Design and Deployment -- 20) ASM Tools and utilities.
Keywords: Oracle (Computer file); Cloud computing; Database management; COMPUTERS / System Administration / Storage & Retrieval